Investigation of mechanical properties and associated microstructure of reactive magnesia cement synthesized from reject brine - Sun, Fanxi (2018)
This study investigates production scaling up of MgO cement synthesized from reject brine and evaluates the mechanical properties and microstructures of the resulting MgO cement. Hydration process and carbonation degree of the resulting MgO mortar were investigated and compared with commercial MgO cement. Compressive strength, scanning electron microscopy (SEM), X-ray powder diffraction (XRD), particle size analysis, acid reactivity, and thermogravimetric and differential thermal analysis (TG/DTA) were engaged for sample characterization. Results showed that MgO cement synthesized from reject brine possesses higher mechanical strength of 32.5 MPa at the age of 28 days as compared to the commercial MgO cement (20.1 MPa). This is mainly attributed to the high reactivity of the synthesized MgO cement as revealed by the microstructure study.